The Development of Training Curriculum for Enhancing the Professional Ability of "Double-Qualified" Accounting Teachers in Vocational Colleges in Guangxi Zhuang Autonomous Region, People’s Republic of China - Yanxiao, Wei; Prachanant, Nawamin; Buranaphansak, Ketsuda (Journal of Roi Kaensarn Academi, 2024)
The purposes of this study were: 1) to study the current states, problems and needs on the professional ability of “double-qualified” accounting teachers; 2) to develop the training curriculum; 3) to implement the training curriculum; and 4) to evaluate the training curriculum for enhancing the professional ability of “double-qualified” accounting teachers in vocational colleges in Guangxi Zhuang Autonomous Region, People’s Republic of China. This study was divided into four phases: Phase 1 - Studying the current states, problems and needs on the professional ability of “double-qualified” accounting teachers. The samples included 30 accounting teachers out of all 60 teachers from Guangxi International Business Vocational College, selected by using 50% technique of the whole population. A questionnaire was designed to assess the professional ability of “double-qualified” accounting teachers. The obtained data were analyzed by using frequency, percentage, mean and standard deviation; Phase 2 - Developing the training curriculum. The target group was six stakeholders: three deputy directors, and three accounting department heads, who were asked to participate in a semi-structured interview guides. Content analysis technique was performed on the interview data; Phase 3 - Implementing the training curriculum. The target group included 20 accounting teachers at Guangxi International Business Vocational College, selected by volunteering basis. The instrument was the test used as pre- and post-tests. The collected data were analyzed by using mean, standard deviation and dependent samples t-test; Phase 4 - Evaluating the training curriculum. The target groups were 20 accounting teachers and five experts. The research instruments were satisfaction questionnaire and questionnaire for evaluating the quality of the training curriculum. The data were analyzed by using mean and standard deviation. The findings could be summarized as follows: The professional ability of “double-qualified” accounting teachers included two dimensions: accounting professional ability and teacher professional ability was at a high level both in overall and each dimension. In terms of accounting professional ability dimension, it was found that the highest to lowest mean scores were accounting professional values, followed by accounting professional knowledge, and accounting professional skills, respectively. In terms of teacher professional ability dimension, it was found that the highest to lowest mean scores were teacher professional ethics and literacy, followed by basic knowledge and application abilities, professional teaching abilities, scientific development and social service abilities, and practical teaching abilities, respectively. The developed training curriculum included three modules: accounting professional skills, scientific development and social service abilities, and practical teaching abilities. Each module was trained for 3 days, totally 9 days for 55 hours. The developed curriculum comprised both theoretical learning and practical exercises. The results of the training curriculum showed that the professional ability of double-qualified accounting teachers was statistical significantly higher than after the training of Module 1: Accounting professional skills, Module 2: Practical teaching abilities and Module 3: Scientific development and social service abilities at the level of .01, and the training curriculum was effective and feasible. The accounting teachers in vocational colleges were satisfied towards the professional ability double-qualified training curriculum at the highest level. In addition, the quality evaluation of the feasibility, propriety, accuracy, comprehensiveness and utility of the training curriculum in overall verified by seven experts was at the highest level. The highest mean score was the quality of utility, followed by accuracy, propriety, feasibility, and comprehensiveness, respectively.